Publishing Construction Contracts and Outcome Details - Kenny, Charles (2012)
Construction governance failures can lead to the construction of the wrong infrastructure, poor quality construction, and excessively high prices for work. There is some evidence from both other sectors and the construction sector itself that improved transparency, especially when combined with oversight, can improve development outcomes through its impact on the quality of governance. This paper reviews that evidence, discusses costs and benefits of greater transparency in particular with regard to the contracting and delivery process in construction, and briefly discusses an initiative to improve governance in public construction -- the Construction Sector Transparency Initiative.